Textbook of hand eczema - Alikhan, Ali; Lachapelle, Jean-Marie; Maibach, Howard I. (New York Springer-Heidelberg, 2014)
Hand eczema is a major complaint worldwide and a frequent occupational disorder. This book provides a comprehensive and detailed overview of the classification, etiology, diagnosis, prevention, and therapy of hand eczema. It is innovative, up to date, and practical. The links with particular occupations are explained, the various diagnostic tests are presented, and the role of different topical and systemic treatments is clearly described. The authors are world leaders in the field. The Textbook of Hand Eczema reflects a new era in hand dermatitis and will be invaluable for all who deal with the condition in their clinical practice. --
From the Contents: AN INTRODUCTION TO HAND ECZEMA -- An Anatomoclinical Approach -- Biometric Characteristics -- Clinical Subtypes and Categorization -- Nail Alterations in Hand Eczema -- Other Dermatoses -- Irritant versus Allergic Contact Dermatitis: An Etiopathological Approach -- A Scope of the Problem: Epidemiology -- Risk Factors -- DETAILS OF SELECTED SUBTYPES OF HAND ECZEMA -- Chemical Skin Burns and Hand Eczema -- Mechanical Trauma and Hand Eczema -- Irritant Contact Dermatitis -- Atopic Hand Eczema -- Pompholyx -- Hyperkeratotic Eczema (Psoriasis) of the Palms -- SPECIAL OCCUPATIONS AT RISK FOR HAND ECZEMA -- Hairdressers{u2019} Eczema -- Occupational Eczema by Metalworking Fluids -- Hand Dermatitis from Acrylate Compounds in Dentistry -- Hand Eczema from Rubber Gloves -- Hand Eczema in the Construction Industry -- DIAGNOSTIC TESTING IN HAND ECZEMA -- Methods for Testing Irritation Potential -- Noninvasive Bioengineering Methods to Predict Skin Irritation -- Acute Irritancy Testing -- Patch Testing -- Prick Testing -- PREVENTION AND TREATMENT OF HAND ECZEMA.
Keywords: Hand; Medicine; Hand Dermatoses; Dermatology; Medicine